Struma Ovarii associated with Pseudo-Meigs Syndrome and elevated serum Ca 125: Case report and literature review - Morales, Oyuki A.; Araiza, Junior J.; Dominguez, Tania P. Alvarez; Guzmán, Rafael Medrano; Barbabosa, Jorge A.; Sosa, Maria I. Tolentino (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Struma Ovarii is a highly specialized monodermal teratoma in which the major component is thyroid tissue. Its relationship with Pseudo Meigs syndrome, hyperthyroidism and elevation of Ca 125 is a rare condition; this could mimic malignancy. Ultrasound and axial tomography may be useful in diagnosis; but histopathological criteria play a very important role in the definitive diagnosis. Our objective is to present a case report of Struma ovarii, ascites, pleural effusion (pseudo meigs syndrome), elevation of Ca 125, hyperthyroidism, and review the published literature in relation to epidemiology and diagnostic characteristics.